What Schools Can Do to Help Disadvantaged Children. (Education Digest, 1987)
This article presents a report on several ways in which schools can help disadvantaged children. This report recommends actions for improving the education of disadvantaged children. Schools must use symbols and public recognition to reinforce school goals and develop school pride. Meetings in parents' homes can create support for raised expectations. Campaigns to repair and repaint school buildings or to tidy up the grounds can make the school a source of local pride. A dress code, school logo, and academic competitions also develop positive bonds between students and school. Successful school leaders move on to address academic achievement and find ways to consolidate gains. In managing a changing school, the principal must stay on top of day-to-day operations, find ways to make new practices routine, and maintain morale. Teachers and principals may be the most influential adults in many youngsters' lives. A punctual, diligent, enthusiastic teacher sets a standard for students; a teacher's willingness to discuss students' problems conveys the message that students are valued.